2016
DOI: 10.12659/msm.896693
|View full text |Cite
|
Sign up to set email alerts
|

Association of HMGB1 Gene Polymorphisms with Risk of Colorectal Cancer in a Chinese Population

Abstract: BackgroundColorectal cancer (CRC) is one of the leading causes of cancer-related deaths worldwide. More advanced work is required in the detection of biomarkers for CRC susceptibility and prognosis. High-mobility group box-1 (HMGB1) is an angiogenesis-related gene reported to be associated with the development of CRC. The direct evidence of HMGB1 gene polymorphisms as biomarkers for CRC has not been reported previously.Material/MethodsA total of 240 CRC patients and 480 healthy controls were periodically enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
(33 reference statements)
1
10
0
Order By: Relevance
“…From RAGE gene, four polymorphisms including rs1800625 (promoter region), rs1800624 (promoter region), rs2070600 (exon 3) and rs184003 (intron 7) were selected. These polymorphisms were widely studied in predisposition to a variety of cancer types, including breast cancer [ 33 ], gastric cancer [ 34 , 35 ], colorectal cancer [ 29 , 36 ], lung cancer [ 37 , 38 ] and so on.…”
Section: Methodsmentioning
confidence: 99%
“…From RAGE gene, four polymorphisms including rs1800625 (promoter region), rs1800624 (promoter region), rs2070600 (exon 3) and rs184003 (intron 7) were selected. These polymorphisms were widely studied in predisposition to a variety of cancer types, including breast cancer [ 33 ], gastric cancer [ 34 , 35 ], colorectal cancer [ 29 , 36 ], lung cancer [ 37 , 38 ] and so on.…”
Section: Methodsmentioning
confidence: 99%
“…However, the results of our study have demonstrated that the HMGB1 polymorphisms rs1412125, rs1045411, and rs1360485 were associated with prostate cancer disease progression and severity ( Table 3 , Table 4 and Table 5 ), suggesting more consistency of HMGB1 SNPs in the oncogenicity of various cancers. In contrast, we found that the HMGB1 rs2249825 polymorphic variants showed no significant association with prostate cancer susceptibility ( Table 2 ) or the clinical status of prostate cancer, suggesting a difference from colorectal cancer [ 33 ] and cervical cancer [ 47 ]. Besides, our previous study found that urothelial cell carcinoma (UCC) patients who carry at least one T allele of the HMGB1 rs1045411 polymorphism had a lower risk and less invasive disease [ 50 ].…”
Section: Discussionmentioning
confidence: 90%
“…The role of HMGB1 SNPs in cancer risk, disease progression, and tumor development remains controversial. Some studies have associated HMGB1 SNPs with increased cancer risk, disease susceptibility, severity, and progression, or poorer response to treatment [ 22 , 23 , 27 , 31 , 33 , 42 , 46 , 47 , 48 , 49 ]. However, other studies have indicated that the HMGB1 SNPs are associated with a lower risk of cancer and a less invasive disease [ 26 , 50 ], or may even not be associated with the risk of cancer [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The full texts of 19 articles were reviewed, and an additional 9 articles were excluded (with 8 articles excluded for not providing usable data and 1 article excluded due to the duplication of the same article in different languages); thus, 10 studies remained for further review. One study 24 whose distribution of genotype deviated from Hardy-Weinberg equilibrium (HWE) ( p HWE < 0.05) in the control was also included in this study but was excluded from the sensitivity analysis.…”
Section: Resultsmentioning
confidence: 99%